2008
DOI: 10.1007/s00383-008-2236-3
|View full text |Cite
|
Sign up to set email alerts
|

Fistula in ano in infants: who recurs?

Abstract: Fistula in ano in infants is a relatively benign process with most children having no serious sequelae. However, a not insignificant portion (13%) of children developed recurrences. Older children who developed fistulas were more likely to have a recurrence than younger, and children who had previous episodes of perianal abscess or pus noted at the time of surgery were more likely to recur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 11 publications
0
10
1
Order By: Relevance
“…The risks from general anesthesia and surgery for these diseases are limited, but they cannot be eliminated completely. In addition, recurrence rates after operation are not ignorable [7,12,15,17]. Therefore, when we consider our results, as well as those of previous studies [1,5,6], conservative treatment of perianal abscess and fistula-in-ano could be the first choice of treatment.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The risks from general anesthesia and surgery for these diseases are limited, but they cannot be eliminated completely. In addition, recurrence rates after operation are not ignorable [7,12,15,17]. Therefore, when we consider our results, as well as those of previous studies [1,5,6], conservative treatment of perianal abscess and fistula-in-ano could be the first choice of treatment.…”
Section: Discussionmentioning
confidence: 75%
“…Traditionally, surgical management of perianal abscess and fistula-in-ano has been the accepted treatment [7,8,12,14,15]. Incision and drainage is the most common procedure used for perianal abscess, and fistulotomy or fistulectomy, which has no difference in the recurrence rate [7,14] although few reports advocated the fistulectomy [15,16], has been the popular surgical treatment of fistula-in-ano.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibiotics are frequently initiated by pediatricians before surgical referral [5]. Complications of surgical management include recurrence, delayed and/or impaired healing, and bleeding [13]. Complications of surgical management include recurrence, delayed and/or impaired healing, and bleeding [13].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors advocated that the probing of the abscess with fistulotomy under general anesthesia reduced the recurrence rates of perianal abscess and fistula-inano. 9,10) Another author reported that a diligent search for the fistulous tract by excessive probing of perianal abscess might lead to iatrogenic fistula formation. 11) Although surgical treatment is a widely accepted therapy for fistula-in-ano, it was recently suggested that fistula-in-ano in infants is a time-limited disorder and fistulotomy or fistulectomy should be avoided.…”
mentioning
confidence: 99%